Synthesis of Organic Coagulant: Poly-diallyldimethyl Ammonium Chloride (PDADMAC) for Treatment of Sewage - Tshukudu, Tiroyaone; Zheng, Huaili; Yang, Jun (Asian Journal of Chemistry, 2013)
In this research, poly-diallyldimethyl ammonium chloride (PDADMAC) was synthesized using the Taguchi method of design of experiments and optimum synthesis conditions were determined. In addition, evaluation of treatment efficiency was determined by measuring both the reduction of residual turbidity and chemical oxygen demand (COD). The results show that the combination of factors adopted as optimum conditions using the Taguchi method were 50 ºC, 0.15 g, 10 mL and 8 h for synthesis temperature, mass of the initiator, volume of de-ionized water and synthesis time, respectively. In addition, the ANOVA results indicate the synthesis temperature and the mass of the initiator played a key role on the synthesis of the PDADMAC. The optimal removal efficiency was achieved at coagulant dosage, pH value, flash mixing speed and settling time of 12 mg/L, 9, 300 rpm and 2 h, respectively. Under optimum conditions, the removal efficiency was 90.71 and 76.54 % for residual turbidity and COD.